Osmotic pressure studied of poly (dimethyl siloxane) / Maimunah Sokro, Arba'at Hassan and Hanita Othman - Sokro, Maimunah; Hassan, Arba'at; Othman, Hanita (2006)
The osmotic pressure, p of poly (dimethyl siloxane), PDMS solutions in trans-decalin was measured over the temperature range of 20 to 40°C at concentrations from 0.5 to 15 wt. %. It was found that the mixing enthalpy H and mixing entropy S of trans-decalin, determined from the temperature dependence of the osmotic pressure, were negative and that the magnitude of H was slightly larger than that of TS. This indicated that the dissolution of the polymers in trans-decalin was dominated by enthalpy or intermolecular interaction. The existence of local structure in the solution was revealed by negative entropy. Virial coefficients were determined from the concentration dependence of the osmotic pressure. The second virial coefficient of PDMS-trans-decalin solution increased linearly with an increased in temperature, and suggested the existence of one temperature. The third virial coefficient of PDMS-trans- decalin solution increased at lower temperatures.